Simultaneous exposure to microplastics and heavy metal lead induces oxidative stress, histopathological damage, and immune dysfunction in marine mussel Mytilus coruscus - Chuanyue Chen; Xueer Wang; Yingrong Jin; Yinchang Yao; Suchang Li; Zhi Liao; Xiaolin Zhang; Xiaojun Yan (Ecotoxicology and Environmental Safety)
The increasing deposition of microplastics (MPs) in aquatic ecosystems is a worldwide concern. MPs can interact with other environmental pollutants, such as heavy metals, and change their toxicity. In this study, we focused on the effects of MPs and lead (Pb), as a toxic heavy metal, on marine mussel Mytilus coruscus under separate and co-exposure situations at environmentally relevant concentrations: MPs (1 mg/L) and Pb (50 μg/L). We found that MPs alone or in combination with Pb significantly decreased the respiration and filtration rates of the mussels (p < 0.05). Histological observations revealed varying extents of damage to the gill and digestive gland caused by a single exposure to MPs, which was aggravated by co-exposure to Pb. In addition, co-exposure induced a higher level of oxidative stress, which was reflected by an increase in hydrogen peroxide and malondialdehyde content, and a decrease in antioxidant enzyme activity. Meanwhile, co-exposure poses a significant threat to the immune function of the mussels, as evidenced by induction of hemocytes to produce excess reactive oxygen species (ROS), significantly reducing lysosome activity (p < 0.05), inhibiting the expression of autophagy-related genes, and inducing the expression of apoptosis-related genes, resulting in hemocyte apoptosis. Furthermore, the TLR/MyD88/NFκB signaling pathway is involved in the immune response of mussels to environmental stress. This study provides novel perspectives on the toxicity of MPs combined with Pb in marine animals, as well as the molecular mechanisms underlying their ecotoxicological effects.